Self-assembly in aqueous solution of amphiphilic graft copolymers from oxidized carboxymethylcellulose - Bordallo, Eduardo [UNESP]; Rieumont, Jacques; Tiera, Marcio José [UNESP]; Gómez, Manuel; Lazzari, Massimo (Elsevier B.V., 2015)
A series of oxidized carboxymethylcellulose-graft-poly(ethylene glycol)-dodecylamine (0CMC-g-PEG-DDA) was prepared by using an appositely prepared PEG with terminal amino groups and different amounts of DDA. The nanoaggregates formed in aqueous solution were characterized by surface tension measurements, fluorescence spectroscopy, dynamic light scattering (DES) and scanning electron microscopies (SEM and TEM). The micelles showed narrow hydrodynamic size distributions and diameters varying from 163 to 193 nm depending on the ratio of DDA to PEG chains. The DDA content in the graft copolymers also affected the core shell interfacial compactness.
Keywords: Carboxymethylcellulose; Amphiphilic graft copolymer; Micellization; PEGylation; Fluorescence